2007
DOI: 10.1177/0145721707309807
|View full text |Cite
|
Sign up to set email alerts
|

Does Patient Blood Glucose Monitoring Improve Diabetes Control?

Abstract: SMBG may be effective in controlling blood glucose for patients with type 2 diabetes. There is a need for studies that implement all the components of the process for self-regulation of SMBG to assess whether patient use of SMBG will improve HbA1c levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 52 publications
(123 reference statements)
2
69
0
Order By: Relevance
“…The American Diabetes Association and other experts recommend self-monitoring of blood glucose (SMBG) as an integral part of diabetes care, although there are mixed results regarding effectiveness in controlling blood glucose for patients with T2DM (McAndrew et al 2007). A recent review of SMBG studies using glycosolated hemoglobin (HgbA1c) as the primary outcome variable (McAndrew et al 2007), found positive, nonsignificant, and negative effects of SMBG in different study designs. The majority of RCTs (Farmer et al 2007) showed improvements in HgbA1c for monitoring conditions compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…The American Diabetes Association and other experts recommend self-monitoring of blood glucose (SMBG) as an integral part of diabetes care, although there are mixed results regarding effectiveness in controlling blood glucose for patients with T2DM (McAndrew et al 2007). A recent review of SMBG studies using glycosolated hemoglobin (HgbA1c) as the primary outcome variable (McAndrew et al 2007), found positive, nonsignificant, and negative effects of SMBG in different study designs. The majority of RCTs (Farmer et al 2007) showed improvements in HgbA1c for monitoring conditions compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…(20)(21)(22) In this study, the calculated sample size was 75 patients per group, which was inflated by 1.2 times to take into account an expected dropout rate of 20%. Even though the sample size was not achieved, we managed to find statistical significance because the change in HbA1c levels was larger than expected (1.3% instead of 1.0%).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the vast majority of prior SMBG research is lacking is a conceptual foundation for the mechanisms that underlie the relationship between SMBG testing and decision-making. Some reviews of prior literature offer a conceptual framework to explain SMBG efficacy (Aalto & Uutela,1997;McAndrew, Schneider, Burns, & Leventhal, 2007;Wing, Epstein, Nowalk, & Lamparski,1986), but there are few research studies built on a conceptual model. Though prior research has been helpful in providing information about overt patient-and provider-cognitions and -emotions surrounding this facet of diabetes selfmanagement, the data tends to be frequency driven and does not consider health decisionmaking.…”
Section: Self-monitoring Of Blood Glucose Literature and Theorymentioning
confidence: 99%